Implementing Computational Thinking Skills in Socio Scientific Issue (SSI) of Force Material Around Us at Elementary School - Yanti Yuli; Kalifah Diah Rizki Nur; Hidayah Nurul (E3S Web of Conferences, 2024)
Computational thinking is a sophisticated problem-solving approach based on computer science. Implementing computational thinking in elementary schools remains a challenge for education, particularly for teachers and students. Teachers must construct learning experiences using computational thinking to make the learning process more engaging, while students must solve issues logically, systematically, and effectively. This study aims to present an overview of the application of computational thinking in natural and social sciences (IPAS) learning and identify its application in fifth-grade elementary school students. The research employed a qualitative research design with a single one-shot case study. The research subjects were 40 fifth-grade students and four teachers. This investigation was conducted during a single meeting that followed the lesson plan for the force material around us. The findings revealed that (a) analysis of student activity data yielded a percentage of 81.25%; (b) the data analysis of student responses to learning yielded favorable results, approaching 100%. According to interviews and observations of CT (Computational Thinking) in SSI (Socio-scientific Issue) in IPAS subjects, implementing CT learning on the forces around us might bring up aspects of the CT foundation, such as pattern recognition decomposition, abstraction, and algorithms. The learning scenario is that students are requested to assess many types of activities that occur in everyday life. Additionally, students will outline various actions that use force.